(untitled) (Acta Scientiarum. Biological Sciences, 2021)
This research assessed the fumigant activity of the essential oil from Piper sancti-felicis Trel and five of its components on the Tribolium castaneum (Herbst) biological model. Hydrodistillation was used for extraction of the essential oil, with separation and identification of the compounds through gas chromatography coupled to mass spectrometry (GC-MS). The fumigant was evaluated through gas dispersion on the T. castaneum. The majority compounds found in the EO were b-nerolidol (15.4%), 3-carene (14.9%), p-cymene (9.1%), spathulenol (8.2%), a-cubebene (6.2%) and calamenene (5.2%). Piper sancti-felicis displayed fumigant activity with a LC50 = 108.5 Î¼g L-1 air, and other individual monoterpenes tested such as Î±-terpinolene (LC50 = 110.1 Î¼g L-1 air), p-cymene (LC50 = 120.3 Î¼g L-1 air), 3-carene (LC50 = 130.6 Î¼g L-1 air), (R) -limonene (CL50 = 189.6 Î¼g L-1 air), and a-pinene (LC50 = 213.1 Î¼g L-1 air), were significantly less toxic than methyl pyrimiphos used as a positive control, CL50 = 87.4 Î¼g L-1 air. The essential oil of P. sancti-felicis can be considered as a natural source of biocides.